2014
DOI: 10.1002/elan.201400085
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsically Porous Polymer Protects Catalytic Gold Particles for Enzymeless Glucose Oxidation

Abstract: The enzymeless glucose oxidation process readily occurs on nano‐gold electrocatalyst at pH 7, but it is highly susceptible to poisoning (competitive binding), for example from protein or chloride. Is it shown here that gold nanoparticle catalyst can be protected against poisoning by a polymer of intrinsic microporosity (PIM‐EA‐TB with BET surface area 1027 m2 g−1). This PIM material when protonated, achieves a triple catalyst protection effect by (i) size selective repulsion of larger protein molecules (albumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…Recently, a novel class of microporous organic materials, polymers with intrinsic microporosity (PIM), has been developed. There are a range of potential applications in gas membrane technology [15,16], in electrolyte media as ionic diode [17], and in electrochemical technology [18,19]. The structurally highly…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a novel class of microporous organic materials, polymers with intrinsic microporosity (PIM), has been developed. There are a range of potential applications in gas membrane technology [15,16], in electrolyte media as ionic diode [17], and in electrochemical technology [18,19]. The structurally highly…”
Section: Introductionmentioning
confidence: 99%
“…PIMs [23,24] provide a new generation of highly rigid microporous materials with (i) excellent processability, (ii) highly rigid pore structures in which guest catalyst molecules can be readily embedded, (iii) good access of solvent and substrate to the catalyst through rigid pores and (iv) robustness towards corrosion. In our previous work, the poly-amine structure PIM-EA-TB [25] (synthesised based on a Tröger's base reaction [26][27][28]) has been employed to electrochemically grow palladium lamellae [29], to act as a host for molecular Fe(II)-porphyrinato electrocatalyst [30] and to protect gold nanoparticles [31] and fuel cell catalysts [32]. Recently, we have demonstrated proof of concept for the immobilisation of the molecular electrocatalyst 4-benzoyloxy-TEMPO (or 4B-TEMPO) into a porous PIM-EA-TB host film for the electrocatalytic oxidation of saccharides [33].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, voltammetric responses for the silver microparticles are more stable and repeatable. Within the potential range studied here PIM-EA-TB has no direct electrochemical activity [13,14] and it can be considered both cation and anion conducting [15]. Generally, with the PIM-EA-TB coating applied features such as the position of oxidation and back-reduction voltammetric responses are maintained and also the complex peak shape observed during the reduction is retained.…”
Section: Resultsmentioning
confidence: 97%
“…It has been demonstrated that metal nanoparticle catalysts can be PIM-coated and thereby protected against poisoning [13] and against detrimental loss and corrosion processes [14]. Here, we employ an intrinsically microporous polymer (PIM) material based on an ethanoanthracene (EA) building block that was synthesised employing a Tröger base (TB) method (PIM-EA-TB [15], see molecular structure in Fig.…”
Section: Introductionmentioning
confidence: 99%